SYMBOLS OF ARMENIA AND THE ROLE OF THE MEDIA IN SHAPING THE IMAGE OF THE COUNTRY (Proceedings of the YSU C: Geological and Geographical Sciences, 2021)
Interest in the formation of the state's image in the era of global competition is extremely. It takes effort to create an image, since this is a conscious creativity aimed at creating a certain, pre-programmed image. The geographical component of the image of a country, region, tourist destination is the basis for building its external and internal image. Any state has its adherents Thanks to these people the symbols of the country are created, which then fly around the world. Armenia is no exception in this sense. Competent promotion of the country's symbols in the media space creates a sense of an established image.
Keywords: geographic image; image; state symbol; Ararat; duduk; apricot; pomegranate; grapes; Armenia; wine; cognac; media